Compulsory licensing as a remedy against excessive pricing of life-saving medicines - Behrang Kianzad (South Centre, 2024)
The COVID-19 crisis intensified decade-long debates on the interaction between intellectual property rights (IPRs), competition law and access to affordable life-saving treatments and vaccines. Compulsory licensing of patented medicines is a tried-and-tested method to expand access, particularly in a situation of "national emergency or other circumstances of extreme urgency" within the meaning of Article 31(b) of the TRIPS Agreement. Some legislations, such as European competition law, offer a toolbox for curbing the exercise of IPRs if they would be found in conflict with certain competition rules, such as rules prohibiting excessive pricing by dominant undertakings. The paper analyses the interface between intellectual property law and competition law in general, moving on to the settled case law of the Court of Justice of the European Union (CJEU) on this matter. It provides a general overview of legal and economics arguments related to excessive pricing prohibition and the main case law of European competition law on the matter and discusses whether compulsory licensing as a remedy against excessive pricing of patented life-saving pharmaceutical products can be a viable and appropriate remedy. Finally, the paper offers policy recommendations relating to compulsory licensing based on excessive pricing.
Keywords: 300; Access to Medicines; Access to Vaccines; Affordable Medicines; Article 31 TRIPS; Competition Law; Compulsory Licenses; Compulsory Licensing; COVID-19; Essential Mediciness; European Union (EU); Innovation; Intellectual Property; Intellectual Property Rights (IPRs); Pandemic; Patent; Pharmaceuticals; Public Health; TRIPS; TRIPS Agreement; TRIPS Flexibilities; TRIPS Waiver; Vaccines